ANALISIS KUALITAS DAN PERSEPSI NILAI TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Pengguna Smartphone di Surakarta) - Eka Dewi S., Ida Ayu Kade Rachmawati Kusasih, Hestin Mutmainah & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the influence of information quality, system quality, service quality, and perception of value influence to Smartphone user satisfaction in Surakarta. The object of research is the Smartphone users who become the sample. The results showed that both partially and simultaneously the quality of information, system quality, service quality, and value perception have an effect on customer satisfaction of Smartphone user in Surakarta. Keywords: information quality, system quality, service quality, perception of value, customer satisfaction